PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) TERHADAP HASIL BELAJAR DALAM PEMBELAJARAN MATEMATIKA PADA MATERI PERBANDINGAN KELAS VII SMP - Patandungan, Elisa Berlin; Pitoy, Cori; Tumalun, Nicky K (Dharmas Education Journal (DE_Journal), 2023)
The learning problem experienced by students is a lack of concentration when the teacher explains the material. Teachers still do not involve students in the teaching and learning process activities. The purpose of this research is to determine the differences in student learning outcomes taught with the STAD model and the Direct Instruction (DI) model on comparative material. This survey was conducted at SMPN 8 Bitung in the 2022/2023 academic year. The type of research used is quantitative with a posttest only control group design. The sample selection was chosen through pretest results from the three classes. Based on the pretest scores, the same and homogeneous classes were classes VII A and VII B. Through drawing lots, class VII A was the control class and VII B was the experimental class. The data collection technique is a test at the end of the meeting. Learning outcomes are obtained from student learning outcome data obtained from the final exam (posttest) in the form of a test. Research statistics were analyzed using a test of two means (t test) which showed that tcount=1.991 > ttable=1.677 with H0 rejected in the difference of two means test (t-test) at the real level α = 0.05. This shows that the average learning outcomes of students taught using the STAD type cooperative learning model are higher than the average learning outcomes of students taught using the DI model in comparative material.